Skills practice manual for LaFleur Brooks' Health unit coordinating - Gillingham, Elaine A.; Wadsworth Seibel, Monica Melzer (Elsevier, 2014)
Includes 96 exercises and activities. This title provides hands-on experience by specifying necessary skills, as well as the materials and steps you need to practice them